2008
DOI: 10.1523/jneurosci.3708-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death after Spinal Cord Injury Is Exacerbated by Rapid TNFα-Induced Trafficking of GluR2-Lacking AMPARs to the Plasma Membrane

Abstract: Glutamate, the major excitatory neurotransmitter in the CNS, is implicated in both normal neurotransmission and excitotoxicity. Numerous in vitro findings indicate that the ionotropic glutamate receptor, AMPAR, can rapidly traffic from intracellular stores to the plasma membrane, altering neuronal excitability. These receptor trafficking events are thought to be involved in CNS plasticity as well as learning and memory. AMPAR trafficking has recently been shown to be regulated by glial release of the proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
192
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(208 citation statements)
references
References 43 publications
14
192
1
Order By: Relevance
“…Because TNFα has been shown to induce surface expression changes of AMPA‐type glutamate receptors (AMPARs), leading to excitotoxicity (Ferguson et al, 2008; Leonoudakis et al, 2008; Santello and Volterra, 2012), we hypothesized that the aberrant release of TNFα by mutFUS astrocytes may also lead to AMPA receptor dysregulation in motor neurons. To test this, we treated motor neurons with ACM from WTFUS or mutFUS‐expressing astrocytes and stained them for glutamate receptor 1 (GluA1), glutamate receptor 2 (GluA2) and microtubule‐associated protein 2 (MAP2) as dendritic marker.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because TNFα has been shown to induce surface expression changes of AMPA‐type glutamate receptors (AMPARs), leading to excitotoxicity (Ferguson et al, 2008; Leonoudakis et al, 2008; Santello and Volterra, 2012), we hypothesized that the aberrant release of TNFα by mutFUS astrocytes may also lead to AMPA receptor dysregulation in motor neurons. To test this, we treated motor neurons with ACM from WTFUS or mutFUS‐expressing astrocytes and stained them for glutamate receptor 1 (GluA1), glutamate receptor 2 (GluA2) and microtubule‐associated protein 2 (MAP2) as dendritic marker.…”
Section: Resultsmentioning
confidence: 99%
“…TNFα is a pleiotropic molecule that can be produced by a number of different cell‐types, including astrocytes (Chung and Benveniste, 1990; Santello and Volterra, 2012). In the CNS in particular, TNFα signaling is complex, and its role in regulating synaptic transmission both physiologically and pathologically is increasingly being appreciated (Ferguson et al, 2008; Leonoudakis et al, 2008; Olmos and Lladó, 2014; Santello and Volterra, 2012). Importantly, soluble recombinant TNFα has been shown to be directly toxic to human fetal tissue derived neurons and motor neuron‐like NSC‐34 in vitro and knockout of TNFα receptors prevents motor neuron cell death in an axonal injury mouse model, indicating that TNFα can damage motor neurons (D'Souza, Alinauskas, McCrea, Goodyer, & Antel, 1995; He, Wen, & Strong, 2002; Raivich et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Especially in the acute phase after injury, activated macrophages and microglia produce various proinflammatory cytokines, such as IL-1β and TNFα, 32,33 and contribute to secondary tissue damage, neuronal loss and demyelination. [34][35][36] Recent studies have demonstrated that inhibition of mTOR suppresses macrophage/microglia activation and reduces neuroinflammation. 22 These findings suggest that inhibition of mTOR can suppress macrophage/microglia activation and reduce the inflammation that causes secondary damage following SCI.…”
Section: Suppression Of Cellular Senescence and Organismalmentioning
confidence: 99%